Tổng hợp các N-axetyl-3-indolinon - Sung, Trần Văn; Tuyến, Nguyễn Văn; Lộc, Trần Văn; Cường, Phạm Văn (Vietnam Journal of Chemistry, 2014)
A convenient and simple method for the synthesis of N-acyl-3-indolinones was developed. The acylation reaction was carried out by treatment of N-aryl acetamides 5a-c with monochloroacetyl chloride in the presence of aluminium (III) chloride (AlCl3) to give N-[2-(2-chloroacetyl)aryl]acetamides 6a-c and subsequent the intramolecular cyclization of these acetamides by treatment with sodium hydride afforded N-acetyl-3-indolinones (7a-c) in good yields (71-87%).